Online Analysis of Reputation Management Shopee Express PT Shopee Indonesia - Haidul Fikri, Muhammad; Ramadhan, Ridho; Kindi Fadhil, Muhammad; Hardian, Fadli (Educationist: Journal of Educational and Cultural Studies, 2023)
Shopee is one of the leading online shopping platforms in Indonesia. As a leading shopping platform, it's not uncommon for Shopee to receive various issues or bad news regarding services and the features offered. Shopee has just stumbled upon an issue regarding its delivery service on social media Twitter, the issue started with a consumer named Arif Novianto who posted on Twitter regarding his experience when he met a Shopee Express courier who delivered his order. The courier admitted that he received low wages when asked by consumers. Consumers who heard the news then responded by writing a post on Twitter which eventually went viral and Shopee received lots of negative responses regarding this news. In response to this issue, Shopee's management spoke up in order to minimize the issue so that it would not develop further. Dan said that shopee management always listens to input and aspirations from Shopee Express driver partners, and continues to strive to maintain the comfort of all parties.